ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN dan LAIN-LAIN PENDAPATAN YANG SAH TERHADAP BELANJA MODAL DI KABUPATEN/KOTA JAWA TIMUR - Diah Nurdiwaty; Badrus Zaman; Efda Kristinawati (Jurnal Aplikasi Bisnis, 2017)
ABSTRACTThe purpose of this study is to analyze the effect of, (1) Growth of the Appropriations Budget Capital Expenditure on Local Government of Regency / City in East Java province, (2) revenue (PAD against Appropriations Budget Capital Expenditure on Local Government of Regency/City in east Java, (3) the Balance Fund against Appropriations Budget Capital Expenditure on Local Government of Regency / City in east Java province, (4) other Revenues Legitimate against Appropriations Budget Capital Expenditure on Local Government of Regency / City in east Java province, (5 ) Economic Growth, Local Revenue (PAD), Balance Funds and other Revenues Legitimate against Appropriations Budget Capital Expenditure on Local Government of Regency / City in East Java province. Data analysis and hypothesis test using a statistical diskripstif to do classical assumption test and multiple linear regression. The research sample is â€œtotaling samplingâ€ 114 Regency / City. The results of this study are partially showed that the variables Economic Growth and Other Income Legitimate no significant effect on capital expenditure budget allocation. While the Local Revenue and Fund Balance significant effect on capital expenditure budget allocation. While the study was conducted simultaneously Growth, PAD, DBH and Other Income Legitimate significant effect on capital expenditure budget allocation.Â Â ABSTRAKTujuan penelitian ini adalah menganalisis pengaruh, (1) Pertumbuhan Ekonomi, (2) Pendapatan Asli Daerah, (3) Dana Perimbangan terhadap, (4) Lain-lain Pendapatan yang Sah, (5) Pertumbuhan Ekonomi, Pendapatan Asli Daerah (PAD), Dana Perimbangan dan Lain-lain Pendapatan yang Sah, terhadap Pengalokasian Anggaran Belanja Modal pada Pemerintah Daerah Kabupaten/ Kota di Provinsi Jawa Timur. Analisis data dan pengujian hipotesis dilakukan menggunakan statistik diskriptif melalui uji asumsi klasik dan regresi linear berganda. Sampel penelitian ini adalah totaling sampling yaitu 114 Kabupaten/ Kota. Hasil penelitian secara parsial menunjukkan bahwa variabel Pertumbuhan Ekonomi dan Lain-lain Pendapatan yang Sah tidak berpengaruh signifikan terhadap pengalokasian anggaran belanja modal. Sedangkan Pendapatan Asli Daerah dan Dana Perimbangan berpengaruh signifikan terhadap pengalokasian anggaran belanja modal. Sedangkan Penelitian yang dilakukan secara simultan Pertumbuhan Ekonomi, Pendapatan Asli Daerah, Dana Perimbangan, dan Lain-lain Pendapatan yang Sah berpengaruh signifikan terhadap pengalokasian anggaran belanja modal.Â